Exploring the Impact of Celebrity Endorsements on The Attitudes And Purchasing Intention in Instagram - Ragil Asma Saputra; Budi Suharjo; Dadang Sukandar (School of Business, IPB University (SB-IPB), 2019)
The use of celebrities as endorser for companies is becoming a popular way for endorsement. This study aims to identify any differences on the impact of celebrity’s credibility on attitudes towards endorsement (AAD), brand (AB) and purchase intention (PI) in single and multiple celebrity endorsement formats. Questionnaires were administered on a sample of 79 respondents. The data were analyzed using proportion test and Structural Equation Modeling analysis. The results suggest there were no significant differences in consumer perceptions and attitudes in single and multiple celebrity endorsements. Credible celebrities were proven to have direct effects on positive attitude towards endorsements and purchase intention, but the impacts were inconsistent in influcencing the attitude towards brands.Keywords: celebrity credibility, celebrity endorsement, consumer attitudes, purchase intention